Estimating the Effectiveness of Rotavirus Vaccine Schedules. Issue 4 (12th April 2021) - Butler, Anne M.; Breskin, Alexander; Sahrmann, John M.; Brookhart, M. Alan
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Important questions exist regarding the comparative effectiveness of alternative childhood vaccine schedules; however, optimal approaches to studying this complex issue are unclear. Methods: We applied methods for studying dynamic treatment regimens to estimate the comparative effectiveness of different rotavirus vaccine (RV) schedules for preventing acute gastroenteritis-related emergency department (ED) visits or hospitalization. We studied the effectiveness of six separate protocols: one- and two-dose monovalent rotavirus vaccine (RV1); one-, two-, and three-dose pentavalent rotavirus vaccine (RV5); and no RV vaccine. We used data on all infants to estimate the counterfactual cumulative risk for each protocol. Infants were censored when vaccine receipt deviated from the protocol. Inverse probability of censoring-weighted estimation addressed potentially informative censoring by protocol deviations. A nonparametric group-based bootstrap procedure provided statistical inference. Results: The method yielded similar 2-year effectiveness estimates for the full-series protocols; weighted risk difference estimates comparing unvaccinated children to those adherent to either full-series (two-dose RV1, three-dose RV5) corresponded to four fewer hospitalizations and 12 fewer ED visits over the 2-year period per 1, 000 children. We observed dose–response relationships, such that additional doses further reduced risk of acute gastroenteritis. Under a theoretical intervention to fully vaccinate all children, the 2-year risk differences comparing full to observed adherence were 0.04% (95% CI = 0.03%, 0.05%) for hospitalizations and 0.17% (95% CI = 0.14%, 0.19%) for ED visits. Conclusions: The proposed approach can generate important evidence about the consequences of delaying or skipping vaccine doses, and the impact of interventions to improve vaccine schedule adherence.